Perceptions of the neighborhood built environment for walking behavior in older adults living in close proximity - Herbolsheimer, Florian; Mahmood, Atiya; Ungar, Nadine; Michael, Yvonne L.; Oswald, Frank; Chaudhury, Habib (Journal of applied gerontology, 2021)
Past research documents a discordance between perceived and objectively assessed neighborhood environmental features on walking behavior. Therefore, we examined differences in the perception of the same neighborhood built environment. Participants were grouped if they lived 400 m or closer to each other. The perception of the pedestrian infrastructure, neighborhood aesthetics, safety from crime, and safety from traffic was derived from a telephone survey from two North American metropolitan areas; 173 individuals were clustered into 42 groups. Older adults who walked for transport in their neighborhood experienced the same neighborhood as more walkable (β = .19; p = .011) with better pedestrian infrastructure (β = .16; p = .037). Older adults with physical limitations experienced the same neighborhood as less safe from crime (β = −.17; p = .030) and traffic (β = −.20; p = .009). The study supports the notion that individual behavior and physical restrictions alter the environment’s perception and explains part of the discordance between objective and subjective assessment of the neighborhood environment.
First published online December 22, 2020
Gesehen am 23.11.2023